THE EFFECT OF BODY CHECKING POLICY CHANGE ON CONTACT MECHANISMS IN 13 AND 14 YEAR OLD YOUTH ICE HOCKEY PLAYERS. Issue 4 (1st February 2017) - Martinez, German; Janzen, Leticia; Krolikowski, Maciej; Romanow, Nicole; Palacios-Derflingher, Luz; Goulet, Claude; Nadeau, Luc; Emery, Carolyn
Abstract : Background: A 2015, Hockey Calgary body checking (BC) policy change disallowed BC from non-elite Bantam (ages 13–14, lower 60% of divisions). This was informed by evidence that disallowing BC in Pee Wee (ages 11–12) reduced the risk of injury, specifically concussion, by >3-fold. Objective: To compare the frequency of type and intensity of player-to-player contacts (PC) and head contact in non-elite Bantam ice hockey games in leagues allowing BC (2014–15) compared with leagues disallowing BC (2015–16). Design: Cohort study. Setting: Ice-hockey arenas in Calgary, Canada. Participants: Non-elite Bantam players in 2014–15 (n=348 players) and 2015–16 (n=309 players) seasons. Interventions: In the 2014–15 season, non-elite Bantam leagues allowed BC. In 2015–2016, BC was disallowed. Main Outcome Measurements: Thirteen games pre-policy change (2014–2015) and 13 post-policy change were video recorded. Analysis using validated methodology was used to compare the frequency, type (i.e., trunk, head and other types of PC with limb/head/stick), and intensity (trunk contacts level 1–5 with increasing intensity) of PCs. Incidence rate ratios (IRR) were estimated using Poisson regression (controlling for cluster by team, offset by player minutes). Results: There were a total of 3485 trunk contacts and 1395 other contacts in 26 games. The overall risk of trunk PCs was lower post-policy change (IRR=0.50, 95% CI; 0.45–0.56). Post-policy change, high intensity (body checking - level 4, 5) contacts decreased (IRR4 =0.19, 95% CI; 0.13–0.26 IRR5 =0.11, 95% CI; 0.03–0.51), lower intensity (level 2, 3) PCs were less frequent (IRR2 =0.45, 95% CI; 0.40–0.50 and IRR3 =0.47, 95% CI; 0.35–0.63), and other contacts made with the limb/stick also decreased (IRR=0.60, 95% CI; 0.48–0.73). Head contact decreased (IRR=0.40, 95% CI; 0.25–0.61). Conclusions: Post-policy change disallowing BC in non-elite Bantam, incidence of high intensity (level 4, 5) PCs decreased 82%. Head contact decreased 60% and stick/limbs contact decreased 40%. These findings inform the mechanisms of injury explaining concussion risk reduction post-BC policy change.